Total Versus Ionized Calcium: Valid Index of Calcium Status in Critically Ill Patients - Madhumita Das; Argha Baruah (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Accurate evaluation of calcium status is essential in critically ill patients. However, reliance on total calcium (tCa) and albumin-corrected calcium often leads to misclassification, influencing clinical decisions. Objective.— To compare various calcium measurement methods with ionized calcium (iCa), the gold standard, and evaluate their diagnostic and prognostic relevance in intensive care unit (ICU) patients. Design.— A cross-sectional study was conducted for 1 year in 145 ICU patients at a tertiary care center. Measured parameters included tCa, iCa, albumin, total protein, and pH. Derived indices included albumin-corrected calcium (CtCa), calculated iCa (CiCa), pH-adjusted iCa (pHiCa), nonionized calcium (NiCa), and the iCa:CtCa ratio. Correlations, sensitivity/specificity, classification accuracy, and receiver operating characteristic (ROC) analyses were performed. Results.— Abnormal iCa levels were observed in 82.07% (119 of 145) of patients, with hypercalcemia being rare. tCa, CtCa, CiCa, and NiCa significantly underestimated hypocalcemia when compared to iCa ( P ≤ .01). Among methods, pHiCa showed the best diagnostic performance (95.2% accuracy; 86.3% sensitivity) and strongest correlation with iCa ( r = 0.983). The iCa:CtCa ratio reflected physiological changes such as alkalosis and hypoalbuminemia, particularly in postoperative and septic patients. ROC analysis indicated poor prognostic value of iCa for prolonged ICU stay. The calculated areas under the curve for ICU stay and mortality were 0.51 and 0.54, respectively. Conclusions.— Conventional calcium measurement methods frequently misclassify calcium status in critically ill patients. pHiCa demonstrated superior diagnostic accuracy and agreement with iCa. While iCa lacks prognostic utility for ICU outcomes, it remains indispensable for precise calcium assessment.